Human and Computer Personality Prediction From Digital Footprints. (April 2019) - Hinds, Joanne; Joinson, Adam
Is it possible to judge someone accurately from his or her online activity? The Internet provides vast opportunities for individuals to present themselves in different ways, from simple self-enhancement to malicious identity fraud. We often rely on our Internet-based judgments of others to make decisions, such as whom to socialize with, date, or employ. Recently, personality-perception researchers have turned to studying social media and digital devices in order to ask whether a person's digital traces can reveal aspects of his or her identity. Simultaneously, advances in "big data" analytics have demonstrated that computer algorithms can predict individuals' traits from their digital traces. In this article, we address three questions: What do we currently know about human- and computer-based personality assessments? How accurate are these assessments? Where are these fields heading? We discuss trends in the current findings, provide an overview of methodological approaches, and recommend directions for future research.